The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10863-016-9692-6
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil improves post-fatigue tension in slow skeletal muscle fibers by modulating glutathione redox state

Abstract: Fatigue is a phenomenon in which force reduction has been linked to impairment of several biochemical processes. In skeletal muscle, the ATP-sensitive potassium channels (K) are actively involved in myoprotection against metabolic stress. They are present in sarcolemma and mitochondria (mitoK channels). K channel openers like nicorandil has been recognized for their ability to protect skeletal muscle from ischemia-reperfusion injury, however, the effects of nicorandil on fatigue in slow skeletal muscle fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…An assay of thiobarbituric acid reactive substances (TBARS) was used as a marker of lipid peroxidation in soleus and gastrocnemius muscles according to the method described by our group 23 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An assay of thiobarbituric acid reactive substances (TBARS) was used as a marker of lipid peroxidation in soleus and gastrocnemius muscles according to the method described by our group 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Nicorandil has been recognized to have clinical significance 16 . Researchers have reported effects of nicorandil on cardiovascular diseases, protecting against ischemia-reperfusion injury in heart [17][18][19][20] , and in skeletal muscle [21][22][23] . Nicorandil has an action linked with its functions as K ATP channel opener 17,24,25 , nitric oxide donor activity 18,19 , and cell antioxidant capacity enhancer [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, glibenclamide was claimed to affect the muscle IGF-1 expression and muscle protein content (12). Nicorandil was chosen as a channel opener due to its hyperkalemic effect, its effect on skeletal muscle contractility, its claimed relation to IGF-1 expression, and the claim of being a myopathic drug (22)(23)(24).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Different studies 15 17 have demonstrated the capacity of NMPG to reduce the deleterious effects of ROS in injuries caused by cardiac ischemia. This product has also been used in vitro to counteract high oxidative stress conditions in rat pheochromocytoma (PC12) cells 18 , skeletal muscle fibers 19 and human prostate cancer cells 20 .…”
Section: Introductionmentioning
confidence: 99%